Investigating the causal association of postpartum depression with cerebrovascular diseases and cognitive impairment: a Mendelian randomization study - Li, Jia; Li, Jinqiu; Shen, Lan; Wang, Huan; Zheng, Tian; Hui, Ying; Li, Xiaoxuan (Frontiers in Psychiatry, 2023)
Background: Postpartum depression (PPD) is considered the most widespread puerperium complication. The associations of major depressive disorder with certain types of cerebrovascular diseases and cognitive function have been proposed, but the potential causal effects of PPD on these phenotypes are still unknown. Methods: A Mendelian randomization (MR) research design with various methods (e.g., inverse-variance weighted method and MR pleiotropy residual sum and outlier test) was adopted to establish a causal relationship of PPD with cerebrovascular diseases and cognitive impairment. Results: No causal relationship of PPD with carotid intima media thickness and cerebrovascular diseases (i.e., stroke, ischemic stroke, cerebral aneurysm) was found. However, MR analyses indicated a causal association between PPD and decreased cognitive function (P = 3.55×10-3) which remained significant even after multiple comparison correction using the Bonferroni method. Sensitivity analyses using weighted median and MR-Egger methods indicated a consistent direction of association. Conclusions: The causal association of PPD with cognitive impairment suggests that cognitive impairment is a critical aspect of PPD and thus cannot be regarded as an epiphenomenon. Addressing cognitive impairment and lessening the symptoms associated with PPD independently play significant roles in the treatment of PPD.